The affective and political economy of hate journalism: Toxic masculinity, misogynism and homophobia in Greek extreme right-wing media - Siapera, Eugenia; Papadopoulou, Lambrini (The Greek Review of Social Research, 2023)
This article focuses on the Greek far-right newspaper Makeleio and aims to record and analyze the way it produces and circulates negative emotions such as hate. We argue that Makeleio which constitutes a successful endeavor has managed to survive and even thrive in Greece’s media landscape by mirroring, reproducing, and reinforcing the misogynist and homophobic values of conservative Greece. It is no coincidence that this kind of journalism flourished during the crisis that hit severely Greece creating uncertainty as the new normal across all aspects of life. This context functioned as a catalyst leading to a wider use of emotions in journalistic practice as a means to address and manage the profound uncertainty. By practicing this kind of ‘hate journalism’, Makeleio creates a special relationship with its readers, who recognize their own language, thoughts, and moral values in its pages. Ultimately, Makeleio mobilizes hate towards women and homosexuals to attract its audience who in their turn support this kind of journalism by consuming it.